Austrian Labor Theory and Preferences Over Compensation - Krause, Martin (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2014)
Personnel Economics has allowed us to better understand compensation schemes in face of the problems coming out of the principal-agent relationship, with individuals pursuing their own private interests making necessary a mechanism to promote the alignment of interests within the organization. The theory had to simplify its assumptions. Austrian Economics Theory, emphasizing subjective value and entrepreneurial creativity gives a convenient background to consider individuals’ preferences over incentives.